Thickness and uniformity analysis of thin and heat-resistant targets - Fisichella Maria; Delaunay Franck; Capirossi Vittoria; Pinna Federico; Calvo Daniela; Campostrini Matteo; Cappuzzello Francesco; Cavallaro Manuela; Iazzi Felice; Massara Antonio; Rigato Valentino; Ursino Martina (EPJ Web of Conferences, 2023)
The thickness and uniformity characterisation of the first prototypes of thin tellurium and germanium targets evaporated on Highly Oriented Pyrolytic Graphite for NUMEN project is reported. The contribution of such targets to the energy resolution on reaction ejectiles is evaluated.